2019
DOI: 10.1038/s41598-018-37216-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association study of body weight and feed efficiency traits in a commercial broiler chicken population, a re-visitation

Abstract: Genome wide association study was conducted using a mixed linear model (MLM) approach that accounted for family structure to identify single nucleotide polymorphisms (SNPs) and candidate genes associated with body weight (BW) and feed efficiency (FE) traits in a broiler chicken population. The results of the MLM approach were compared with the results of a general linear model approach that does not take family structure in to account. In total, 11 quantitative trait loci (QTL) and 21 SNPs, were identified to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
(74 reference statements)
5
27
0
Order By: Relevance
“…Hence, the increase in the heritability estimates across the selection trajectory attest the increase in genetic variance is not only due to scale effects rather it may be attributed to accumulation of new mutuations or other genetic effects that are not properly accounted in the statistical model. This is consistent with the reported results in chapter 5 (Mebratie et al, 2019) in which we have detected a number of QTL regions and candidate genes associated with BW and FE traits even though birds were pre-selected for BW and undergone several generations of selection for FE. In fact, the increase in genetic variance of quantitative traits from the accumulation of new mutations has been known for quite some time (Hill, 2000;.…”
Section: Effects Of Selection On Body Weight and Feed Efficiencysupporting
confidence: 92%
See 4 more Smart Citations
“…Hence, the increase in the heritability estimates across the selection trajectory attest the increase in genetic variance is not only due to scale effects rather it may be attributed to accumulation of new mutuations or other genetic effects that are not properly accounted in the statistical model. This is consistent with the reported results in chapter 5 (Mebratie et al, 2019) in which we have detected a number of QTL regions and candidate genes associated with BW and FE traits even though birds were pre-selected for BW and undergone several generations of selection for FE. In fact, the increase in genetic variance of quantitative traits from the accumulation of new mutations has been known for quite some time (Hill, 2000;.…”
Section: Effects Of Selection On Body Weight and Feed Efficiencysupporting
confidence: 92%
“…The genetic correlations of BW between different ages is also shown to decrease as the distance between BW measurements increased suggesting that BW at "early age" and "late age" is partly controlled by different genes which might be related to change in the physiological system of birds with age as explained by stating that there could be genes that "turn on" and "turn off" as an animal ages causing changes in physiology and performance. This is consistent with our results in chapter 5 (Mebratie et al, 2019) where we have identified age specific Quantitative trait locus (QTL) regions; different QTLs and candidate genes were identified to be associated with BW at three different ages with only a little overlap between the identified QTL regions and candidate genes across the three ages. The reported overlap in QTL and candidate genes were for BW measurements that were taken closer together than those recorded far apart.…”
Section: Age By Genotype Interactionsupporting
confidence: 91%
See 3 more Smart Citations